2007
DOI: 10.1093/glycob/cwm054
|View full text |Cite
|
Sign up to set email alerts
|

Pectin induces apoptosis in human prostate cancer cells: correlation of apoptotic function with pectin structure

Abstract: Treatment options for androgen-independent prostate cancer cells are limited. Therefore, it is critical to identify agents that induce death of both androgen-responsive and androgen-insensitive cells. Here we demonstrate that a product of plant cell walls, pectin, is capable of inducing apoptosis in androgen-responsive (LNCaP) and androgen-independent (LNCaP C4-2) human prostate cancer cells. Commercially available fractionated pectin powder (FPP) induced apoptosis (approximately 40-fold above non-treated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(129 citation statements)
references
References 46 publications
3
115
0
4
Order By: Relevance
“…The extracted pectins of citrus peel and apples are used as a gelling and stabilizing agent in food and cosmetic industries. Pectins within the fruits and vegetables are part of the daily dietary fiber and have multiple positive effects on human health including lowering cholesterol, serum glucose levels, decrease occurrence of diabetes and cancer [17][18][19]. This points the relevance of pectins in diverse emerging fields of study, even in human health.…”
Section: Pectinsmentioning
confidence: 99%
“…The extracted pectins of citrus peel and apples are used as a gelling and stabilizing agent in food and cosmetic industries. Pectins within the fruits and vegetables are part of the daily dietary fiber and have multiple positive effects on human health including lowering cholesterol, serum glucose levels, decrease occurrence of diabetes and cancer [17][18][19]. This points the relevance of pectins in diverse emerging fields of study, even in human health.…”
Section: Pectinsmentioning
confidence: 99%
“…Jackson et al (2007) have shown that commercially available plant pectin is effectively capable to induce apoptosis in androgen responsive LNCap and androgen independent LNcaP-C4-2 prostate cancer cells compared with CP, pH modified CP or pectaSol suggesting that specific structural elements within pectin are responsible for the apoptotic activity. In the case of colon cancer cells, Cheng et al (2011) have demonstrated that treatment of HT-29 human colon cancer cells with temperature modified HG-rich pectin dramatically increased anti-proliferative effect in the cells.…”
Section: Pectin Mcp and Cancer Cell Apoptosismentioning
confidence: 99%
“…They provide structural support in primary walls, influence secondary wall formation in fibers and woody tissues, and are a reservoir of oligosaccharide signaling molecules (1,(7)(8)(9). The gelling and stabilizing properties of pectin are exploited for food enhancement and industrial purposes, and pectin has multiple health benefits including lowering cholesterol and serum glucose levels, inhibiting cancer growth and metastasis, and prebiotic function in the gut (10)(11)(12)(13).…”
mentioning
confidence: 99%